Self-powered and light-adaptable stretchable electrochromic display - Wu, Wenting (2023)
A stretchable electrochromic display with a self-powered feature is an attractive concept in addressing the demands of information visualization and interaction without an external power supply for next-generation wearable and portable electronics. Herein, a self-powered stretchable electrochromic display is proposed for the first time, with WO3 on the stretchable conductor as the electrochromic electrode integrated in parallel with the Zn/carbon electrodes and topped with a ZnCl2-based organohydrogel. This geometrically designed electrochromic device can be self-colored by the chemical potential gap between WO3/Zn electrodes. The self-bleaching process caused by the oxidation of the reduced WO3 electrode is facilitated by the leakage current between the WO3/carbon electrodes. In this constructed self-powered system, the electrochromic electrode shows reversible coloring/bleaching performance up to 50% strain and maintains favorable stability with power-free reversible electrochemical switching for 400 cycles. Optical contrast retention at 81% is maintained for 200 stretching/recovery cycles. The prepared device combined with a phosphorescent substrate is demonstrated as a light-adaptable stretchable display, where the “on/off” states of the display are shown in both bright and dark conditions without power consumption. This work provides broad application prospects for futuristic multifunctional stretchable and portable display electronics.